Study of the art of facial expressions in the emotion of irony - César, Carla Patrícia Hernandez Alves Ribeiro; Guedes-Granzotti, Raphaela Barroso; Sordi, Claudia; da Silva, Kelly (Seven Editora, 2024)
Irony, regardless of its subtype, is routinely used in human communication. Verbal, vocal, and non-verbal resources are used to express the irony. In this chapter, the objective is to present a literature review on using irony through facial expression. According to the results obtained, the face can express irony, highlighting the contradiction between oral speech and the facial expression itself, which helps the receiver understand that the speech is ironic. There are still scientific gaps on the subject, and more researchers must investigate the topic. DOI:https://doi.org/10.56238/sevened2024.016-006